2023
DOI: 10.1029/2023ea002905
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Surface Deformation and Its Intrinsic Mechanism in Shenzhen, China Using Sentinel‐1A SAR Imagery

Abstract: To avoid disasters caused by surface deformation in urban areas, monitoring and analyzing the mechanism of surface deformation in urban areas on a large scale and in long‐term series is mandatory. Based on PS‐InSAR technology and using 157 Sentinel‐1A images, the surface deformation in Shenzhen was monitored from 2015 to 2022, and the obtained deformation rate ranged from −22.8 to +23.2 mm/year. In this paper, analysis is presented by integrating urbanization, climate, and geology data from Shenzhen. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Ferretti et al's research showed that under the condition that the absolute value of the residual phase is less than 𝜋 , the deformation velocity difference ∆𝑣 and the elevation error ∆𝜀 can be estimated by maximizing the phase coherence coefficient model of M interferograms, with the objective function as follows [37]:…”
Section: Ps-insar Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Ferretti et al's research showed that under the condition that the absolute value of the residual phase is less than 𝜋 , the deformation velocity difference ∆𝑣 and the elevation error ∆𝜀 can be estimated by maximizing the phase coherence coefficient model of M interferograms, with the objective function as follows [37]:…”
Section: Ps-insar Techniquementioning
confidence: 99%
“…This method determines a certain number of "Persistent Scatterers (PS)" and then processes the pixels around each PS point. PS points need to satisfy two conditions: first, they must be stable; and second, they can be detected by the Synthetic Aperture Radar (SAR) antenna through proper orientation [37].…”
Section: Ps-insar Data Processingmentioning
confidence: 99%
“…Ferretti et al's research showed that under the condition of the absolute value of the residual phase being less than π, the deformation velocity difference ∆v and the elevation error ∆ε can be estimated by maximizing the phase coherence coefficient model of M interferograms, with the objective function as follows [39]:…”
Section: Ps-insar Techniquementioning
confidence: 99%
“…They similarly identified land subsidence in the coastal areas and metro construction zones in western Shenzhen. Zhou, Liu [30] were the first to discover land subsidence near the Qinglinjing Reservoir in Shenzhen. They combined geological expertise to analyze the causative factors, attributing them to the engineering geological conditions in the area.…”
Section: Introductionmentioning
confidence: 99%